2001
DOI: 10.1002/eat.1101
|View full text |Cite
|
Sign up to set email alerts
|

Eating disturbance and sexual trauma in childhood and adulthood

Abstract: This study provides additional support for the association between childhood sexual abuse and eating disorder behavior. Childhood sexual abuse may be particularly linked to the presence of binge eating behavior and several other forms of impulsive self-destructive behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
95
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(108 citation statements)
references
References 37 publications
11
95
0
2
Order By: Relevance
“…In particular, several clinical and population studies, both retrospective and prospective, suggest that CM plays a role as a predisposing factor for the later onset of different psychiatric symptoms and disorders, such as major depression, post-traumatic stress disorder, drug abuse, anxiety symptoms, dissociation, body dysmorphic and eating disorders, psychotic experiences and personality disorder. 5,[12][13][14][15][16][17][18][19][20][21] Moreover, several studies have focused on the negative impact of CM on body image, both in a nonclinical sample and in subjects with eating disorders. 17,18,22 It is often difficult to ascertain the meaningful link between CM and adult psychopathology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, several clinical and population studies, both retrospective and prospective, suggest that CM plays a role as a predisposing factor for the later onset of different psychiatric symptoms and disorders, such as major depression, post-traumatic stress disorder, drug abuse, anxiety symptoms, dissociation, body dysmorphic and eating disorders, psychotic experiences and personality disorder. 5,[12][13][14][15][16][17][18][19][20][21] Moreover, several studies have focused on the negative impact of CM on body image, both in a nonclinical sample and in subjects with eating disorders. 17,18,22 It is often difficult to ascertain the meaningful link between CM and adult psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…5,[12][13][14][15][16][17][18][19][20][21] Moreover, several studies have focused on the negative impact of CM on body image, both in a nonclinical sample and in subjects with eating disorders. 17,18,22 It is often difficult to ascertain the meaningful link between CM and adult psychopathology. This is because of the frequent co-occurrence of other possible risk factors, such as other adverse life events or, conversely, of positive modifying factors (for example, success at school or in sport activities, supportive family environment).…”
Section: Introductionmentioning
confidence: 99%
“…For example, high rates of co-morbidity between NSSI and substance use are commonly reported (Putnins, 1995;Beutrais et al, 1996;Kessler et al, 1999;Hilt et al, 2008), although not invariably found (Dulit et al, 1994;Soloff et al, 1994). There is also a well-documented link between NSSI and eating disorders (Favazza et al, 1989;Favaro and Santonastaso, 2000;Wonderlich, 2001;Dohm, 2002;Paul, 2002;Sansone and Levitt, 2002;Stein et al, 2004; but see also Zlotnick et al, 1999). Rates of self-injury are also elevated six-fold in people who have been exposed to physical acts of violence or threats to their lives (Berenson et al, 2001).…”
mentioning
confidence: 99%
“…The topic of mediating factors is worthy of exploring as it might aid counsellors helping those with AN if an anorexic client has a history of childhood sexual abuse, OCD, depression, borderline personality disorder, or posttraumatic stress disorder (Everill & Waller, 1995;Wonderlich et al, 2001). It is also a necessary to present the mediating factors, as they may help guide treatment options and intervention techniques.…”
Section: Mediating Factorsmentioning
confidence: 99%
“…Clinicians have long argued that childhood sexual abuse is a risk factor for the development of AN (Ackard & Neumark-Sztainer, 2003;Barnes, Emberson, Golding, 2005;Briere & Scott, 2007;Cachelin, Schug, Juarez, & Monreal, 2005;Everill & Waller, 1995;Johnson et al, 2002;Smolak & Murnen, 2001;Wonderlich et al, 2001). The issue is whether a meaningful relationship exists between the two phenomena, or whether it is merely an illusory one because of the prevalence of both in a female population (Connors & Morse, 1993).…”
Section: Childhood Sexual Abusementioning
confidence: 99%